Physiological and environmental assessment of heat strain risk among welders using the predicted heat strain model - Sahri, Moch.; Jannah, Farahul; Ayu, Friska; Rhomadhoni, Muslikha Nourma; Fasya, Abdul Hakim Zakkiy (International Journal of Occupational Safety and Health, 2026)
Introduction: Welders are routinely exposed to high thermal loads, increasing the risk of heat stress. Environmental indices such as the Wet-Bulb Globe Temperature (WBGT) are commonly used for assessment but do not account for individual physiological responses. This study aimed to evaluate heat strain among welders using the Predicted Heat Strain (PHS) model defined by ISO 7933:2018, which integrates environmental and physiological factors. Methods: An observational study was conducted involving 41 male welders. Environmental parameters—including dry-bulb, wet-bulb, globe temperature, relative humidity, and air velocity—were measured three times during an 8-hour shift using a QUEST Temp° 44 monitor. Metabolic rate was estimated through task observation and standardized values. Predicted water loss was calculated using the PHS model through the FAME Lab PHS Calculator. Statistical analysis, including an independent samples t-test, was performed using Python in Google Colaboratory. Results: All participants experienced predicted water loss exceeding the 5% threshold recommended by ISO 7933:2018, ranging from 6.02% to 14.59%. The average WBGT was 26.11 °C, above the 25 °C limit for very high metabolic workloads. Participants with body weight below 65 kg had significantly higher proportional water loss (mean = 12.29%, SD = 1.62) compared to those with ≥65 kg (mean = 9.11%, SD = 1.51; t = 6.50, p < 0.001). Conclusion: Welders face substantial heat strain risk, particularly those with lower body mass. Combining physiological modeling with environmental assessment offers a more complete evaluation of heat exposure risks. Preventive strategies should address both environmental and individual factors to enhance worker protection.